Vpogledi v dokumentacijo - Smrdel, Borut (Podjetje in delo, 2016)
The paper deals with the problem of access to information, originating from public procurement procedures, focusing mainly on the protection of business secrets. It presents the legal framework regulating this area, the jurisprudence of the National Review Commission for Reviewing Public Procurement Procedures, as well as the judgment of the European Court of Justice in Case Varec, also relevant to the matter. The paper points to a disparity between the requirement of protection of business secrets in procurement procedures on one hand and open access to all the information after the completion of these procedures on the other. In this connection, it expresses the need for a unified approach to the treatment and protection of information originating from public procurement procedures.
Keywords: javna naročila; javni razpisi; pravna ureditev; revizija